Pengembangan Sistem Informasi Prediksi Output Produksi dengan Metode Single Moving Average di Industri Mebel Jepara - Sofia Ulfah; A. Faiq Abror (Lembaga Pengembangan Kinerja Dosen, 2025)
This research develops a production output prediction information system in the Jepara Furniture Industry based on not optimal production so that production planning is needed to minimize overruns in the financing process and increase production efficiency. This system is developed using the software development method with a waterfall model and implements the Single Moving Average (SMA) method in the calculation process of predicting production output. At the Requirement stage, using observation and interview techniques. The Design stage produces an Entity Relationship Diagram (ERD) design, use case disgram. The Implementation stage is the process of developing a system using the PHP programming language and the Laravel framework while implementing design, coding, and the Single Moving Average (SMA) method in the process of calculating production output predictions. At this stage, simulations are carried out with Desert Round Table data in the span of 2024 and the results of the March moving average calculation and April prediction are 82.67. The Testing stage uses blackbox testing related to functionality and feasibility testing using questionnaires with user-friendliness indicators. The results of the feasibility of the system obtained a feasibility rate of 80%. The Maintenance stage is carried out in the system development process obtained from suggestions on the testing process.